Damage localization in hydrogen storage vessel by guided waves based on a real-time monitoring system. (23rd August 2019) - Yang, Bin; Xiang, Yanxun; Xuan, Fu-Zhen; Hu, Chaojie; Xiao, Biao; Zhou, Shaoping; Luo, Chengqiang
Abstracts: This paper presents a new method and builds an online monitoring system for fully automatic detecting and locating defects in a hydrogen storage vessel using guided wave technology. Based on the theoretical background of guided wave that propagating in a hollow sphere and cylinder, coordinate transformation method is adopted to modify the ellipse location algorithm. The modified algorithm is then used to online locating the defects in the cylinder and head section of the hydrogen storage vessel, respectively. Different piezoelectric ceramic transducer (PZT) networks are proposed to excite-receive guided waves and set up sensor path. A 2 × 64 tunnel matrix switch and three software are used to help signal processing and damage detection by the proposed localization algorithm automatically. By calculating the wave amplitude difference between the current and pristine signals, a series of experiments are performed using the online monitoring system. According to the obtained real-time diagnostic images, the exciting frequencies, wave velocities, and PZT arrangement effects on the localization precision are investigated. The results show that, with suitable exciting frequency, wave velocities, and PZT arrangements, the proposed method and the real-time diagnosis system are able to locate the defects in the hydrogen storage vessel accurately. Highlights: We developed a real-time monitoring system for SHM of hydrogen storage vessels. We proposed a discrete strategy to monitor the hydrogen storage vessel. f = 240 and v = 3.75 are suggested for damage localization in hydrogen storage vessel. The system locates the defects in hydrogen storage vessel with error<2.65%.